2001
DOI: 10.1046/j.1365-2265.2001.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro secretion of FSH by cultured clinically nonfunctioning and gonadotroph pituitary adenomas is directly correlated with locally produced levels of activin A

Abstract: It is concluded that levels of activin A, follistatin and FSH in media of cultured nonfunctioning adenomas and gonadotroph adenomas are positively correlated. This suggests that these adenomas secrete FSH in response to the relatively high locally produced levels of activin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Kwekkeboom et al (10) reported no correlation between the amounts of LH and FSH released in vitro and the serum hormone values in 20 patients with NFPAs, but LH and FSH were released in only seven and nine cultures respectively of the 20 tumours studied, making correlations difficult to interpret. We were able to compare data from 38 subjects and found no correlation for LH but did demonstrate a significant correlation for FSH, as has been shown previously by Wessels et al (18) in a small study of patients with gonadotrophinomas (n ¼ 4) and NFPAs (n ¼ 14). This positive correlation between serum and media FSH suggests that the cultures are reflecting the in vivo situation as far as FSH secretion is involved.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Kwekkeboom et al (10) reported no correlation between the amounts of LH and FSH released in vitro and the serum hormone values in 20 patients with NFPAs, but LH and FSH were released in only seven and nine cultures respectively of the 20 tumours studied, making correlations difficult to interpret. We were able to compare data from 38 subjects and found no correlation for LH but did demonstrate a significant correlation for FSH, as has been shown previously by Wessels et al (18) in a small study of patients with gonadotrophinomas (n ¼ 4) and NFPAs (n ¼ 14). This positive correlation between serum and media FSH suggests that the cultures are reflecting the in vivo situation as far as FSH secretion is involved.…”
Section: Discussionsupporting
confidence: 61%
“…At the pituitary level, activin acts in a local manner to stimulate FSH expression and secretion and has an antiproliferative effect, with these actions being blocked by follistatin and inhibin (21). A positive correlation has been demonstrated in NFPAs between activin and FSH by two groups (17,18). Other studies have shown that the antiproliferative effect of activin may be lost in some gonadotrophinomas (22).…”
Section: Discussionmentioning
confidence: 89%
“…Transforming growth factor-a (TGF-a), epidermal growth factor (EGF), and their common tyrosin kinase receptor (EGF-R) are overexpressed in pituitary adenomas, particularly in those with high aggressiveness (32)(33)(34)(35). Moreover, in gonadotroph adenomas activin/inhibin subunits appear highly expressed together with the specific type I and type II receptors while follistatin, which prevents activin action by binding this subunit, is reduced (36)(37)(38). Among the members of the fibroblast growth factor (FGF) and receptor family, particular attention has been paid to FGF-2 and FGF-4, both showing mitogenic and angiogenic activity (4,(39)(40)(41)(42).…”
Section: Genetics Of Pituitarytumorsmentioning
confidence: 99%
“…Moreover, gonadotrope cells produce follistatin, a TGF-β ligand that binds activin and blocks activin actions. In pituitary tumors, activin receptors are highly expressed while follistatin is reduced [50, 51]. Accordingly, it has been proposed that the imbalanced expression of these proteins, resulting in an enhanced activin signaling, may represent a pathogenetic mechanism in the development of this adenoma subtype.…”
Section: Signaling Of Growth Factors In the Pathogenesis Of Pituitarymentioning
confidence: 99%